The Challenge of CRISPR-Cas Toward Bioethics - Gonzalez-Avila, Luis Uriel; Vega-López, Juan Manuel; Pelcastre-Rodríguez, Leda Ivonne; Cabrero-Martínez, Omar Alejandro; Hernández-Cortez, Cecilia; Castro-Escarpulli, Graciela (Frontiers in Microbiology, 2021)
Since determining the structure of the DNA double helix, the study of genes and genome has revolutionized contemporary science; with the decoding of the human genome, new findings have been achieved, including the ability that humans have developed to modify genetic sequences in vitro. The discovery of gene modification mechanisms as the CRISPR-Cas system (Clustered Regularly Interspaced Short Palindromic Repeats) and Cas (CRISPR associated). Derived from the latest discoveries in genetics, the idea that science has no limits has exploded. However, improvements in genetic engineering allowed access to new possibilities to save lives or generate new treatment options for diseases that are not treatable by using genes and their modification in the genome. With this greater knowledge, the immediate question is who governs the limits of genetic science? The first answer would be the intervention of a legislative branch, with adequate scientific advice, from which the logical answer, bioethics, should result. This term was introduced for the first time by Van Rensselaer Potter, who in 1970 combined the Greek words bios and ethos, Bio-Ethik, which determined the study of the morality of human behavior in science. The approach to this term was introduced to avoid the natural tension that results from the scientific technical development and the ethics of limits. Therefore, associating the use of biotechnology through the CRISPR-Cas system and the regulation through bioethics, aims to monitor the use of techniques and technology, with benefits for humanity, without altering fundamental rights, acting with moral and ethical principles.